Postawa polityczna Żydów w zaborze rosyjskim na przełomie XIX i XX wieku w świetle analizy ruchu narodowodemokratycznego i demokratyczno-postępowego - Sobczak, Mieczysław (The Jews political attitude in the Russian sector of partitioned Poland at the turn of the 19th century towards Polish national-democratic and democratic-progressive ideology, 2007)
In the article, the author described what had happened that the relation between Jews and Poles became worse at the turn of the 19th century (till the breakout of World War I). In the Russian sector of partitioned Poland it was possible to identify what were the biggest blames from the side of Polish nationalism (the National Democracy) and adherents of democratic-progressive ideology towards Jews. As a result of reciprocation misunderstandings between Poles and Jews arose the attitude of antisemitism and antipolonism. This attitude was dangerous for both sides.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (11); 2007; nr 1188, s. 97-115